2018
DOI: 10.1186/s40101-018-0163-0
|View full text |Cite
|
Sign up to set email alerts
|

Black tea aroma inhibited increase of salivary chromogranin-A after arithmetic tasks

Abstract: BackgroundGrowing attention has been paid to the effects of food flavor components on alleviating negative brain functions caused by stressful lifestyles. In this study, we investigated the alleviating effect of two kinds of black tea aromas on physical and psychological stress induced by the Uchida-Kraepelin test, based on salivary chromogranin-A (CgA) levels as a stress marker and subjective evaluations (Profile of Mood States).ResultsCompared with the water exposure control, inhaling black tea aroma (Darjee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Similarly, green and white tea consumption decreased levels of salivary chromogranin A (CgA), an ANS-mediated indicator of stress level, among university students ( n = 18) performing mental stress load tasks in a randomized cross-over design study [42]. CgA was also found to decrease in two studies that exposed university students to the aromas of black or green tea prior to taking 30-min mental stress load tasks [43,44]. The inhalation of both types of tea aroma induced lower CgA levels following stress load tasks.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…Similarly, green and white tea consumption decreased levels of salivary chromogranin A (CgA), an ANS-mediated indicator of stress level, among university students ( n = 18) performing mental stress load tasks in a randomized cross-over design study [42]. CgA was also found to decrease in two studies that exposed university students to the aromas of black or green tea prior to taking 30-min mental stress load tasks [43,44]. The inhalation of both types of tea aroma induced lower CgA levels following stress load tasks.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…They observed in humans that partner body odor reduced subjective discomfort during a stressful event, as compared with the odor of oneself, which suggests that partner odor is a scent of security, especially for attachment-secure adults. Yoto et al [ 81 ] investigated the alleviating effect of black tea aroma on physical and psychological stress in humans that is induced by the Uchida–Kraepelin test, based on salivary chromogranin-A (CgA) levels as a stress marker and subjective evaluations. It was observed that inhaling black tea aroma can reduce stress levels, and Darjeeling tea aroma tends to improve mood before exposure to mental stress.…”
Section: Olfaction and Stress Response In The Brainmentioning
confidence: 99%
“…Essential oils have been used to regulate autonomic nervous activity, control depression, anxiety, cognitive disorders, insomnia, and stress-related disorders 1 5 . Several studies conducted at various stages in vitro to in vivo have suggested the pharmacological effects of inhaled components in essential oils 6 .…”
Section: Introductionmentioning
confidence: 99%